Resting sympathetic baroreflex sensitivity in subjects with low and high tolerance to central hypovolemia induced by lower body negative pressure - Hinojosa-Laborde, Carmen; Ryan, Kathy L.; Rickards, Caroline A.; Convertino, Victor A. (Frontiers in Physiology, 2014)
Central hypovolemia elicited by orthostasis or hemorrhage triggers sympathetically-mediated baroreflex responses to maintain organ perfusion; these reflexes are less sensitive in patients with orthostatic intolerance, and during conditions of severe blood loss, may result in cardiovascular collapse (decompensatory or circulatory shock). The ability to tolerate central hypovolemia is variable and physiological factors contributing to tolerance are emerging. We tested the hypothesis that resting muscle sympathetic nerve activity (MSNA) and sympathetic baroreflex sensitivity (BRS) are attenuated in male and female subjects who have low tolerance (LT) to central hypovolemia induced by lower body negative pressure (LBNP). MSNA and diastolic arterial pressure (DAP) were recorded in 47 human subjects who subsequently underwent LBNP to tolerance (onset of presyncopal symptoms). LT subjects experienced presyncopal symptoms prior to completing LBNP of -60 mm Hg, and subjects with high tolerance (HT) experienced presyncopal symptoms after completing LBNP after -60 mmHg. Contrary to our hypothesis, resting MSNA burst incidence was not different between LT and HT subjects, and was not related to time to presyncope. BRS was assessed as the slope of the relationship between spontaneous fluctuations in DAP and MSNA during 5 min of supine rest. MSNA burst incidence/DAP correlations were greater than or equal to 0.5 in 37 subjects (LT: n= 9; HT: n=28), and BRS was not different between LT and HT (-1.8 ± 0.3 vs. -2.2 ± 0.2 bursts•(100 beats)-1•mmHg-1, p=0.29). We conclude that tolerance to central hypovolemia is not related to either resting MSNA or sympathetic BRS.